MARITIME BOUNDARY DELIMITATION THE INDONESIAN CASE *) - M.J. Sitepu (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Indonesia is an archipelagic country with two thirds of its territory represented water. The concept of an archipelagic state us an important one to Indonesia, and the marine sector has never been more important to the notion. This importance is reflected in the priority which marine issues have recived from the government, including the instalment of the National Marine Council in September 1996. Maritime boundary issue often concern claims for marine resources. Maritime boundary delimitation is a fundamental strategy to enforce national sovereignty over marine and coastal areas. For Indonesia, accurate marine boundary delimitation is of primary importance to definiting the nature and extent of the country’s marine resources. Maritime boundaries will be drawn on charts and given due publicity. The limit of the territorial sea, contiguous zone, EEZ, and continental self are measured from straight baselines connecting the outermost points of the outermost islands of Indonesia This paper will detail the current status of Indonesia’s maritime boundary delimitation efforts and its future prospect.